Germline DNA damage response gene mutations as predictive biomarkers of immune checkpoint inhibitor efficacy - Dennis, Michael J.; Bylsma, Sophia; Madlensky, Lisa; Pagadala, Meghana S.; Carter, Hannah; Patel, Sandip P. (Frontiers in Immunology, 2024)
Background: Impaired DNA damage response (DDR) can affect immune checkpoint inhibitors (ICI) efficacy and lead to heightened immune activation. We assessed the impact of pathogenic or likely pathogenic (P/LP) germline DDR mutations on ICI response and toxicity. Materials and Methods: A retrospective analysis of 131 cancer patients with germline DNA testing and ICI treatment was performed. Results: Ninety-two patients were DDR-negative (DDR-), and 39 had ≥1 DDR mutation (DDR+). DDR+ patients showed higher objective response rates (ORRs) compared to DDR-in univariate and multivariable analyses, adjusting for age and metastatic disease (62% vs. 23%, unadjusted OR = 5.41; 95% CI, 2.41-12.14; adjusted OR 5.94; 95% CI, 2.35-15.06). Similar results were seen in mismatch repair (MMR), DDR pathways with intact MMR (DDR+MMRi), and homologous recombination (HR) subgroups versus DDR-(adjusted OR MMR = 24.52; 95% CI 2. DDR+MMRi = 4.26; 95% CI, HR = 4.74; 95% CI,. DDR+ patients also had higher ORRs with concurrent chemotherapy (82% vs. 39% DDR-, p=0.03) or concurrent tyrosine kinase inhibitors (50% vs. 5% DDR-, p=0.03). No significant differences in immune-related adverse events were observed between DDR+ and DDR-cohorts. Conclusion: P/LP germline DDR mutations may enhance ICI response without significant additional toxicity.